Holocene climate change inferred from grain‐size analysis in the eastern Alashan Plateau, Inner Mongolia, Northern China. (8th November 2017) - Chen, Shu‐E; Fan, Shuang‐Hu; Liu, Xiu‐Hua
Abstract : A grain‐size analysis in Tonggunao sedimentary profile indicated that 6 arid and 6 wet episodes have been detected in the Holocene, reflecting millennium‐scale climate change. The study area is located in the eastern Alashan Plateau, with the Helan Mountains to the east and the Tengger Desert to the west. It has a vulnerable natural ecology that is sensitive to environmental and climatic changes. The rapid climatic changes revealed by the analysis may be representative of the global climate‐change pattern during the Holocene.